Historical dictionary of Confucianism - Littlejohn, Ronnie, 1949- (Lanham, Maryland : Rowman & Littlefield, 2023)
"Historical Dictionary of Confucianism contains a chronology, an introduction, and an extensive bibliography. The dictionary section has more than 700 cross-referenced entries on terms, personalities, movements, and texts of the tradition as it has made its trek across East Asia, especially to Korea and Japan"--
Includes bibliographical references.
Keywords: Confucianism -- History -- Dictionaries